1997
DOI: 10.1021/es9605681
|View full text |Cite
|
Sign up to set email alerts
|

A Distributed Reactivity Model for Sorption by Soils and Sediments. 6. Mechanistic Implications of Desorption under Supercritical Fluid Conditions

Abstract: Phenanthrene desorption isotherms for five dry soil materials were measured in supercritical carbon dioxide (SC CO 2 ) at up to 12 different temperature (40-60 °C) and pressure (120-310 atm) conditions for each soil. The Freundlich model adequately described all 40 isotherms obtained. At each condition, sorption capacity increased with increasing organic matter content with a positive dependence on oxygen content. Trends in desorption with SC CO 2 temperature and pressure were qualitatively consistent with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 37 publications
(52 reference statements)
1
63
0
Order By: Relevance
“…The dual-sorption model has characterized NOM as two domains containing absorption (partitioning) and adsorption (micropore-filling) phases (Weber and Huang, 1996;Weber and Young, 1997;Xing and Pignatello, 1997;Ran et al, 2003). Kerogen is a form of NOM that has undergone geochemical diagenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The dual-sorption model has characterized NOM as two domains containing absorption (partitioning) and adsorption (micropore-filling) phases (Weber and Huang, 1996;Weber and Young, 1997;Xing and Pignatello, 1997;Ran et al, 2003). Kerogen is a form of NOM that has undergone geochemical diagenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of desorbed protein was determined from the UV absorption values at 280 nm ( Figure 5) and analyzed by SDS-polyacrylamide gel electrophoresis (SDS-PAGE) ( Figures S3 and S4). The Freundlich (equilibrium) model is a commonly used approach for determining reagent distribution between solid and solution for both adsorption and desorption processes [41,42]. We used the Freundlich model to determine cellulase desorption.…”
Section: Adsorption and Desorption Of Wild-type And Mutant Accel12bmentioning
confidence: 99%
“…All figures were described as AcCel12B-PT0 (dashed dotted line and ◊), AcCel12B-PT1 (dotted line and ▲), AcCel12B-wt (dashed line and ○), and AcCel12B-PT3 (solid line and ■). Furthermore, n in Table 5 indicates sorption intensity [44], or the energy of desorption [42]. The n values of wild-type and mutant AcCel12B desorbing from Avicel reduced gradually with the number PT/S-box units in a step of approximately 0.4 per PT/S-box unit added.…”
Section: Adsorption and Desorption Of Wild-type And Mutant Accel12bmentioning
confidence: 99%
“…Supercritical fluid extraction (SFE) with pure carbon dioxide (CO2) has recently been proposed as a potentially rapid method to determine the "availability" of soil-and sediment-bound organics (43)(44)(45)(46)(47). The potential advantage of SFE is that the solubility of target analytes can be varied continuously over several orders of magnitude by controlling the extraction pressure and temperature (48,49).…”
Section: Introductionmentioning
confidence: 99%
“…However, in a recent series of articles, SFE performed under increasingly stronger conditions showed that PCBs were present in several different types of sites on every soil and sediment tested and that PCBs were associated with sites ranging from "fast" (extracted at the mildest SFE conditions) to "slowly desorbing" sites (45)(46)(47). Furthermore, when the same sediments were exposed to PCBs in water for up to 18 days, the exposure time was only sufficient for the PCBs to sorb to only the "fast" sites, demonstrating that very long exposure times would be needed for the PCBs to gain the "slowly desorbing" sites which were occupied in the original environmentally aged sediments (47).…”
Section: Introductionmentioning
confidence: 99%